Pendampingan Penentuan Harga Jual Buku di Penerbit Peneleh - Aji Dedi Mulawarman; M. Fadhir A.I. Lamase; Novrida Qudsi Lutfillah; Febrina Nur Ramadhani; Meryana Rizky Ananda (Penerbit Goodwood, 2022)
Purpose: to overcome problems related to determining the selling price of books appropriately by considering material and non-material aspects. Method: This assistance was carried out at Peneleh Publishers using the Participatory Action Research (PAR) method. Data were collected through observation, Focus Group Discussion, interviews, and documentation. Analysis of the success of the mentoring program can be seen through three indicators, namely knowledge, action, and evaluation. Results: The implementation of the program is carried out in three stages, namely socialization, mentoring, and review. The socialization stage of this program was carried out in 5 meetings. From the socialization stage, information was obtained regarding the problems faced by participants related to setting the selling price of books and giving discounts. The next stage is mentoring. The activities carried out at this stage are identifying material and non-material aspects in determining the selling price of books, identifying differences in the components of determining the selling price of printed books and digital books, calculating the cost of goods sold with the agreed method, determining the pattern calculation of selling prices and book discounts, as well as applying formulas with the designed system. The stage of reviewing the abilities and skills of participants is carried out to evaluate the entire program that has been carried out. Based on the review of the abilities and skills of the participants in determining the selling price of books, it can be said that the abilities and skills of the participants are good. Conclusion: The mentoring program have been achieved well. Participants of the mentoring program can understand the concept and urgency of setting selling prices on their products, be able to identify the components of costs, both material and non-material, understand the right discount calculation pattern, and be able to apply the technique of determining the right selling price for book products. published.